Puccinia coronata Cda. Var. Recording and Hyperparasite Fungus Darluca filum (Biv.)Cast. on the Species Alopecurus myosuroides Huds. In Coastal Region of Syrian (Latakia University Journal -Biological Sciences Series, 2024)
Tow subspecies of Alopecurus myosuroides Huds. were collected. They were: (A. myosuroides subsp. tonsus. and A. myosuroides subsp. myosuroides) during March and April in (2023-2024), from Al- Shalfatiya area in Lattakia.The results of this study showed that both of them were infected by rust fungi Puccinia coronata Cda. Var. In addition of the presence of parasitoid fungus Darluca filum (Biv.) Cast. on P. coronata. The infection rate of D.filum on P.coronata  which infected  the two subspecies A. myosuroides subsp. tonsus., and A. myosuroides subsp. myosuroides was 35% and 30% respectively, while the severity of D.filum on the previous subspecies was counted 50 Pycnidia/cm2 and 42 Pycnidia/cm2 respectively. This is the first record of the fungus D.filum in Syria on Alopecurus myosuroides.